2005
DOI: 10.1007/s00127-005-0922-1
|View full text |Cite
|
Sign up to set email alerts
|

The process of care in residential facilities

Abstract: This study provides naturalistic evidence of the heterogeneity of the process of residential care on a large scale. Future efforts should focus on developing an empirical classification of RFs, as well as on national and international standards of care and staffing to address patients' needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 39 publications
0
25
0
1
Order By: Relevance
“…Patients who require long-term residential care are now catered for by RFs. Detailed information about the quantity and quality of these facilities has been obtained through a nationwide survey of all RFs (the PROGRES study) conducted in 2000-2002 [15][16][17][18][19]. On 31 May 2000, there were 1,370 RFs with 17,138 beds, an average of 12.5 beds each and a rate of 2.98 beds per 10,000 inhabitants.…”
Section: The Italian System Of Residential Carementioning
confidence: 99%
“…Patients who require long-term residential care are now catered for by RFs. Detailed information about the quantity and quality of these facilities has been obtained through a nationwide survey of all RFs (the PROGRES study) conducted in 2000-2002 [15][16][17][18][19]. On 31 May 2000, there were 1,370 RFs with 17,138 beds, an average of 12.5 beds each and a rate of 2.98 beds per 10,000 inhabitants.…”
Section: The Italian System Of Residential Carementioning
confidence: 99%
“…Three quarters of RFs did not formally set any limit to the length of in-stay, resulting in a low turn-over of patients [5,6]. De Girolamo and colleagues found that low turnover was mainly related to higher number of residents, higher number of former mental hospital patients, older age of the patients and fewer full-time staff [5,11].…”
Section: Current Situation and Issues Raisedmentioning
confidence: 99%
“…About 7 percent occupied the space of a former mental hospital [11]. However, the environmental characteristics suggested a home-like atmosphere in many RFs [6]; there was often a garden available, and residents generally lived in two-bed rooms. The quality of life that was observed can be comparable to that of a psychotic outpatient's [21].…”
Section: Current Situation and Issues Raisedmentioning
confidence: 99%
See 2 more Smart Citations